PENGARUH STRESS KERJA DAN MOTIVASI TERHADAP KEPUASAN KERJA KARYAWAN PADA PT. SINARMAS DISTRIBUTOR NUSANTARA CABANG BATURAJA - Syafe’i, Darman; Putriani, Dyah Ayu; ., Ronaldi (Ekonomika, 2024)
This study aimed to determine the influence of work stress and motivation on employees’ job satisfaction at PT. Sinarmas Distributor Nusantara Baturaja Branch. The data for this research were collected through questionnaire distribution. The population size was 36 people. The analysis method used was multiple linear regression. Based on the partial hypothesis testing, work stress (X1) had a significant influence on job satisfaction at PT. Sinarmas Distributor Nusantara Baturaja Branch, and the motivation variable (X2) had a significant influence on job satisfaction (Y) at PT. Sinarmas Distributor Nusantara Baturaja Branch. Simultaneously, work stress (X1) and motivation (X2) had a significant influence on job satisfaction (Y) at PT. Sinarmas Distributor Nusantara Baturaja Branch. The coefficient of determination (R Square) was 0.902, indicating that 90.2% of the contribution to job satisfaction at PT. Sinarmas Distributor Nusantara Baturaja Branch could be explained by the variables of Motivation and work discipline, while the remaining 9.8% was influenced by other variables outside the scope of this study, such as competence (wages or salary, incentives, rewards, and allowances), work ethic, work commitment, human resource empowerment, job satisfaction, and others.